Understanding physical activity in firefighters through a social ecological lens - Brin, Halle (My University, 2026)
Firefighting is a high-risk, physically demanding occupation that requires firefighters to perform tasks in life-threatening situations. Engaging in physical activity (PA) and exercise regularly can mitigate health concerns and enable firefighters to achieve fitness levels to safely perform their job duties. Although PA and exercise barriers among firefighters have been studied previously, including through a Social Ecological Model lens, little is known about how these multilevel influences shape PA participation and how interpersonal, organizational, and environmental exercise supports can be systematically assessed using a firefighter-specific audit tool as one currently does not exist. The purpose of this dissertation was to: 1) explore multilevel influences on firefighters’ on- and off-duty PA; 2) adapt a multilevel workplace PA audit tool for firefighters and evaluate reliability; 3) examine frequencies of multilevel exercise supports and PA behaviors across three fire departments; and 4) examine relationships between audit tool domains and PA volume at different intensities. This dissertation is composed of three studies (Chapters 2, 3, and 4). Methods: In Chapter 2, a mixed-methods study, we explored multilevel influences on both on- and off-duty PA using a survey (N = 32) followed by focus groups (N = 30). Chapter 3 implemented three phases to select, adapt, and pilot test a fire department, exercise-specific audit tool. Fifty-eight firefighters from three career fire departments completed the adapted tool via online survey. Chapter 4 used the newly adapted audit tool to explore differences in fire departments’ exercise supports (N = 58 firefighters), and participants wore accelerometers for 7 consecutive days to examine PA behaviors (n = 44). Results: Chapter 2 found intrinsic motives and self-efficacy to be moderately associated with PA. Several themes emerged indicating firefighters’ PA participation is shaped by peer and family dynamics, departmental norms, operational demands, and their physical environment and resources. Chapter 3 resulted in an adapted Fire Department Multilevel Exercise Supports (FD-MES) tool focused on exercise (i.e., structured PA) using a total of 104 items across five domains. Reliability testing varied across rater comparisons and showed distinct rank-based patterns (e.g., captain vs. firefighters) with captain-to-captain raters having the highest proportion of items (21.2%) considered to have moderate to perfect reliability compared to captain-to-firefighter and firefighter-to-firefighter raters (10.6% and 11.5%, respectively). Many items (38.5%-43.3%) across rater comparisons lacked sufficient variability for kappa estimation. Additional refinement is needed to operationalize terms and improve reliability of some items. Results in Chapter 4 found significant differences between the three fire departments for the Community Assets & Partnership domain and few subdomains. Participants accumulated an average of 56.10 minutes of moderate-to-vigorous PA per on-duty day, with few differences in PA intensities observed between departments. No significant associations were observed between on-duty PA and FD-MES domain or subdomains scores. Conclusions: Qualitative findings suggest multilevel influences shape both PA opportunities and motivation for firefighters. Firefighters may have differing perceptions of their sources and resources for exercise support by rank, emphasizing the need for transparent policies and streamlined expectations across shifts or stations. This discrepancy by rank may reinforce captains and crew leaders to translate policy into daily practices. The FD-MES addresses a critical gap in the literature, as no existing tool comprehensively assesses fire departments’ strengths and areas for improvement related to exercise supports. Although the FD-MES tool needs additional revision to further enhance reliability and validity, it may still be beneficial for fire departments to assess and better understand their department’s support for exercise. The combined information from these studies can help inform policy and leadership practices by identifying actionable opportunities to support firefighter exercise participation, such as considering flexible on-duty exercise policies, improving access to fitness resources, strengthening leadership communication, and establishing avenues for improving PA and exercise promotion efforts across multiple levels within the fire service.
Keywords: Social Ecological Model; Physical activity; Occupational health